Cardiac rehabilitation mortality trends: how far from a true picture are we? - Doherty, Patrick; Rauch, Geraldine (Heart, 2013)
In this issue of Heart , Beauchamp and colleagues paper, entitled ‘Attendance at cardiac rehabilitation is associated with lower all-cause mortality after 14 years of follow-up’, sets high expectations for cardiac rehabilitation (CR) in contributing to a long-term mortality effect.1 The study of 544 patients suggests that the relative increase in mortality risk for non-attenders was 58% compared to attenders (Hazard ratio (HR) 1.58, p=0.004) and that the dose of CR may actually determine the extent of mortality. These findings are substantially higher than previous Cochrane review data, where the mortality effect, for 47 Randomized controlled trials (RCTs), involving 10 794 patients, was (Relative Risk (RR) 0.87) and (RR 0.74) for all-cause mortality and cardiac mortality, respectively.2 When compared with the very low, non-significant, mortality effect (RR 0.98) from the rehabilitation after myocardial infarction trial (RAMIT) study,3 which continues to be debated,4 the 1.58 HR, from Beauchamp and colleagues, is as a polar opposite in terms of mortality benefit. - - The obvious question is, ‘why is there so much variation in mortality estimates involving CR?’ It could be that the Melbourne CR programmes are really that good, but equally the high mortality estimate might be explained by other factors. This editorial will try to clarify the situation while highlighting wider issues and challenges with CR mortality estimates. - - Beauchamp and colleagues1 used retrospective data, from their previous study,5 which originally aimed to ‘identify sociodemographic and clinical predictors of non-attendance and dropout separately for men and women automatically referred to CR programmes’. As the purpose of their first study was to identify differences between attenders and non-attenders,5 it becomes obvious that differences also exist between attendees and dropouts, which question the rationale for combining them and make it difficult to picture the CR context in the follow-up paper. …